Let "f(a,a)=0" be the condition (1) and "f(a,f(b,c))=f(a,b)+c" be the condition (2).
We have
"f(a,b)+b=f(a,f(b,b))=f(a,0)=f(a,f(a,a))=f(a,a)+a=a", that is "f(a,b)=a-b"
So we obtain that if "f" satisfies the conditions (1) and (2), then "f(a,b)" can be only "a-b"
Check whether "f(a,b)=a-b" satisfies the conditions (1) and (2).
We have "f(a,a)=a-a=0", so "f(a,b)=a-b" satisfies the condition (1).
Next, "f(a,f(b,c))=f(a,b-c)=a-(b-c)=(a-b)+c=f(a,b)+c", so "f(a,b)=a-b" satisfies the condition (2).
We obtain that "f" satisfies the conditions (1) and (2) if and only if "f(a,b)=a-b", then "f(3.5;7)=3.5-7=-3.5"
Answer: "-3.5"
Comments
Leave a comment